The Combined Effectiveness of Piriformis Stretch and Muscle Activation Exercises in Patients with Sacroiliac Joint Pain.: Life Sciences-Piriformis Stretch and Muscle Activation for Sacoiliac Joint Pain - Bhupendra Karki; Abhijit Kalita; Abhijit Dutta (International Journal of Life Science and Pharma Research, 2022)
Sacroiliac joint pain is one of the common misdiagnosed orthopedic causes of low back pain, which affects between 15 to 30 percent of individuals with mechanical low back pain below L5. The sacroiliac joint is found out to be a source of dysfunction and pain in 10% to 27% of suspected cases of patients with chronic low back pain. Clinicians use different electrotherapy modalities, biomechanical correction techniques, and exercises for addressing SI joint pain. Many studies have been undertaken to find out the efficacy of different treatment tools in combination or isolation. Likewise, there are studies done to understand the effect of piriformis stretch and muscles activation exercises on sacroiliac joint pain but, there exists very little evidence studying the combined effect of both the treatment tools. So our study aims to determine the combined effect of piriformis stretch and muscles activation exercises in patients with sacroiliac joint pain. About 30 subjects, both male and female with a primary diagnosis of sacroiliac joint pain by the physician were recruited into two groups. Group A having 15 patients received piriformis stretch and muscles activation exercises, and Group B having 15 patients received only muscles activation exercises. All the subjects received therapy sessions thrice weekly for four weeks. Outcome measures used were the visual analog scale (VAS) and oswestry disability index(ODI). Pre- intervention assessment and post-intervention assessment was carried out for both groups and the received data was analyzed using paired and independent t-test. According to the results of the analysis, the average improvement of VAS for Group A and Group B were 2.33 and 3.53 respectively. The paired t-test was 23.129 and 14.270, which is statistically highly significant (p-value = 0.000). The average improvement in oswestry disability index for group A and group B were 16.13 and 26.13 respectively using mean and standard deviation. The paired t-test was 11.014 and 6.934 respectively, which is statistically highly significant (p-value = 0.000). There is a significant improvement in both Group A and Group B. However, Group A (piriformis stretch and muscle activation exercises) showed significant improvement in the treatment of sacroiliac joint pain. The results indicated that both Group A and Group B had significant improvement in the scores of VAS and ODI scores at the 4th week when compared to baseline values, but when comparing the end results of group A and group B, it has been found out that group A intervention is more effective than Group B in treating patients with sacroiliac joint pain. From the data analysis reports, it can be concluded that when these treatment tools i.e piriformis stretch and muscles activation exercises are applied in combination, it gives better results in the management of sacroiliac joint pain